Factors contributing to urban expansion of Shiraz City, Iran - Iraj Karimi, 1971-, author 608733 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Doktor Falsafah (Perancangan Bandar dan Wilayah))